The science of grapevines - Keller, Markus (Horticulturist) (Academic Press, 2020)
The Science of Grapevines, Third Edition reflects the latest insights into cultivar relationships, vascular transport, hormone action, and stress responses of grapevines. Based on the author's many years of teaching, research and practical experience with grapevines and grape production, the book is completely revised and updated, presenting a comprehensive introduction on the physical structure of the grapevine, its organs, their functions, and their environmental interactions. While many concepts discussed are broadly applicable to plants in general, the focus is on grapevines, especially cultivated grapevines. This book enables readers to use these concepts in their own scientific research or in practical production systems. Scientifically grounded and integrating discoveries in other plant species, the book explores the physiological processes underlying grapevine form and function, their developmental and environmental control, and their implications for practical vineyard management. --